Mapping of quantitative trait loci for seminal vesicle mass and litter size to rat chromosome 8 - Zídek, V; Pintír, J; Musilová, A; Bílá, V; Kren, V; Pravenec, M (Journal of reproduction and fertility, 1999)
The spontaneously hypertensive rat (SHR) and the Brown Norway (BN) rat differ significantly in litter size (7.6 versus 4.5 pups). In the HXB and BXH sets of recombinant inbred (RI) strains derived from SHR and BN rats, heritability of litter size and of selected male reproductive parameters such as sperm production, sperm count, sperm morphology and motility, and the mass of the testis, epididymides, and seminal vesicles were estimated and a search was undertaken for quantitative trait loci (QTL) associated with these phenotypes. The mass of seminal vesicles was significantly associated with a QTL near the D8Cebr204S21 marker on chromosome 8 (LOD score = 4.1, P = 0.00001); this QTL was responsible for 46% of the genetic variability of the trait. The same gene marker on chromosome 8 also showed a suggestive association with the litter size. Litter size was significantly correlated with the mass of seminal vesicles (r = 0.58, P = 0.003). These findings indicate that the variability in litter size among RI strains may be due in part to differences in the mass of seminal vesicles and it is possible that both mass of seminal vesicles and litter size are determined by a pleiotropic effect of the same QTL on rat chromosome 8.
Keywords: rekombinace genetická; semenné váčky; Recombination, Genetic; Likelihood Functions; Seminal Vesicles; potkani inbrední BN; Quantitative Trait, Heritable; Phenotype; krysa rodu Rattus; Genotype; zvířata; Regression Analysis; genetická variace; Rats, Inbred BN; Genetic Variation; Male; velikost vrhu; potkani inbrední SHR; fenotyp; Chromosome Mapping; Rats; pravděpodobnostní funkce; genotyp; mapování chromozomů; Animals; mužské pohlaví; Litter Size; Rats, Inbred SHR; kvantitativní znak dědičný; regresní analýza